Efeitos da nutrição mineral na competição inter e intraespecífica de Eucalyptus grandis e brachiaria decumbens: 1- crescimento - Brendolan, Rodrigo Alves; Pellegrini, Marcello Tadeu [UNESP]; Da Costa Aguiar Alves, Pedro Luís [UNESP] (My University, 2000)
The present work was conducted with the objective to study the effects of mineral nutrition on Eucalyptus grandis and Brachiaria decumbens (#BRADC) growth, when submitted to inter- and intra-specific competition. The treatments consisted of two plants of Eucalypts/pot, two plants of BRADC/pot, and one plant of each species/pot. The plants were nourished with the Hoagland e Arnon (1950) complete solution; with no K, P or N; or only with either N, P or K. Sixty days after growing side by side, no effect of the inter- and intra-specific competition on eucalypts plant high, branch number and leaf dry mass was observed. When mineral nutrition did not limit plant growth (complete solution or solution with no K), intra-specific competition reduced on average, 23% of eucalypts root length, leaf area, and stem and root dry mass, and inter-specific competition reduced, on average, 75% of BRADC dry mass. When mineral nutrition became a limiting factor, no plant competition effect on the parameters studied was detected.
Effects of mineral nutrition on inter- and intra-specific competition of Eucalyptus grandis and Brachiaria decumbens: 1- plant growth
Keywords: Brachiaria decumbens; Development; Eucalyptus; Interference; Plant growth; Minerals; Nutrition; Plants (botany); Hardwoods; Eucalyptus Grandis; Growth; Plants